Evaluation of the Effectiveness of Turmeric (Curcuma longa) Extract as a Feed Additive on the Growth and Survival of Common Carp (Cyprinus carpio) - Argi Kusuma; Bambang H. Siswoyo; Helentina M. Manullang (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
This study aimed to evaluate the effect of dietary turmeric extract supplementation on the growth performance and survival rate of common carp. The study was conducted using an experimental method with a completely randomized design (CRD) consisting of four treatments and three replicates: P1 (control), P2 (5% turmeric extract), P3 (10% turmeric extract), and P4 (15% turmeric extract). The observed parameters included weight gain, length gain, survival rate, and water quality variables, namely temperature and pH. The results showed that turmeric extract supplementation had no significant effect (p > 0.05) on the weight or length growth of common carp. However, descriptively, a positive growth trend was observed at the 5% supplementation level, whereas increasing the dose to 15% tended to reduce fish survival. Throughout the study, water quality parameters remained within the tolerance range for common carp and were not considered limiting factors. These findings indicate that turmeric extract was not yet effective as a primary growth promoter; however, it may have potential as a supportive feed additive when applied at low doses. Further studies are recommended to determine a more specific optimal dosage and to include physiological parameters and feed efficiency indices to obtain more comprehensive results.